2020
DOI: 10.1177/0049475520981305
|View full text |Cite
|
Sign up to set email alerts
|

A non-resolving splenic ‘abscess’ in an elderly male – An unusual manifestation of splenic lymphoma

Abstract: Splenic abscess is a relatively uncommon condition, posing a diagnostic and therapeutic challenge for the treating physician. It occurs due to haematogenous spread from endocarditis or other septic foci, especially in immune-compromised individuals and diabetics. We describe an elderly male who presented with splenomegaly and low-grade fever with no predisposing factors. Examination revealed a tender splenomegaly. Ultrasonography (US) showed a hypoechoic area within the spleen from which guided aspiration of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Of particular interest is the presentation of this splenic lymphoma as a continuously‐draining abscess. In the literature review, we identified four reports of splenic lymphoma presenting as an abscess: marginal zone lymphoma [ 12 ], DLBCL [ 13 , 14 ], and Hodgkin lymphoma. [ 15 ] Most similar to our patient was the case of the marginal zone lymphoma; percutaneous drainage, in that case, yielded purulent material that grew Staphylococcus aureus and Klebsiella pneumoniae , but the patient failed to significantly improve with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is the presentation of this splenic lymphoma as a continuously‐draining abscess. In the literature review, we identified four reports of splenic lymphoma presenting as an abscess: marginal zone lymphoma [ 12 ], DLBCL [ 13 , 14 ], and Hodgkin lymphoma. [ 15 ] Most similar to our patient was the case of the marginal zone lymphoma; percutaneous drainage, in that case, yielded purulent material that grew Staphylococcus aureus and Klebsiella pneumoniae , but the patient failed to significantly improve with antibiotics.…”
Section: Discussionmentioning
confidence: 99%